Penerapan Perangkat Multimodel Pada Matakuliah Kimia Fisika II Untuk Mahasiswa S-1 Pendidikan Kimia - Fatayah Fatayah; Kriesna Kharisma Purwanto (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The purpose of this research was to see the successful application of learning by using multimodeled devices in the physics chemistry course II in the Chemistry Education Study Program of Billfath University. The research design used in this study is a descriptive analysis. The object of the study was the course Of Physical Chemistry II (Reaction Rate, Reaction Rate Law, Reaction Order, Determination of reaction order, as well as factors that influence reaction rate). This stage of research consists of two stages, namely pre-research, and applying multimodel learning. Pre-research was carried out with the aim of knowing the initial picture of Physics Chemistry II courses that were considered difficult for most students. The next step is the application of multimodel learning that aims to find out the success of application by using a multimodel device of Physical Chemistry study materials II at the Chemistry Education Study Program FKIP Billfath University. As for knowing the success of learning implementation using multimodel can be measured by the ability of indicators that implement multi models. The results of the analysis found that 80% of students experienced the completeness of studying in the course of Physics Chemistry II. Based on these findings, it can be concluded that the application of learning using multimodel devices in the course of Chemistry Physics II in the Chemistry Education Study Program of Billfath University can be said to have experienced success.